A JURIDICAL REVIEW OF BUSINESS ACTORS’ LIABILITY IN COMPENSATING CONSUMERS FOR LOSSES RESULTING FROM PRODUCT PACKAGING WITHOUT AN EXPIRY DATE - I Made Arismayuda; Putu Eka Trisna Dewi; Cokorde Istri Dian Laksmi Dewi (Warmadewa Press, 2025)
This study aims to identify and analyse the legal protection afforded to consumers who receive products without clear information, as well as the liability of business actors to compensate for any resulting losses, pursuant to Law Number 8 of 1999 on Consumer Protection. The methodological approach employed in this legal research is a normative juridical one. This involves examining primary, secondary, and tertiary legal materials using both normative juridical and qualitative analyses, which are then systematically organised. The findings indicate that the provision in Article 8 Paragraph (1) of the Consumer Protection Law (UUPK) of Indonesia has not been effectively implemented. This is reflected by the existence of business actors who fail to include an expiry date on packaged products in accordance with prevailing regulations. The legal consequences for breaching the requirement to include an expiry date on packaged products may entail administrative sanctions, as stipulated in Article 71 of BPOM Regulation No. 31/2018, Article 61 Paragraph (2) of Government Regulation of the Republic of Indonesia Number 69 of 1999 concerning Food Labelling and Advertising, as well as Articles 62 Paragraph (1) and 63 of the Consumer Protection Law. Such administrative sanctions may include a written warning, temporary suspension of production activities, product recall, and revocation of business licences.